Rethinking Strategy for Gender Equality in Trade Unions - Tjandraningsih, Indrasari (Jurnal Perempuan, 2021)
The non-strategic role and position of women workers in trade union organization, even in the women-dominated sector, is hardly changed even though the number of women members of trade unions is increasing. Various programs have been carried out to increase the strategic role of women in trade union organizations but so far have not shown significant results. Based on interviews with officers of gender equality programs for trade unions, union leaders and women and men members and literature studies this paper offers an idea of the need for a non-exclusive approach and actively and proportionally involving men in awareness-raising and gender equality programs for trade unions. This idea is based on the fact that in trade unions gender-related program is always left to or only involves women. The strategy in the gender equality awareness and improvement program that only involves women causes the program’s effectiveness to be low because half of the causes of the problem is not involved.